The effect of a local promotional campaign on preconceptional lifestyle changes and the use of preconception care. (2nd January 2018) - Poels, Marjolein; van Stel, Henk F.; Franx, Arie; Koster, Maria P. H.
Abstract: Purpose: The objective of this study was to investigate the effect of a local promotional campaign on preconceptional lifestyle changes and the use of preconception care (PCC). Material and methods: This quasi-comparative study was carried out between February 2015 and February 2016 at a community midwifery practice in the Netherlands. The intervention consisted of a dual track approach (i) a promotional campaign for couples who wish to conceive and (ii) a PCC pathway for health care providers. Questionnaires were collected from a sample of women who received antenatal care during the pre-intervention ( n = 283) and post-intervention ( n = 257) period. Main outcome measures were preconceptional lifestyle changes and PCC use (defined as searching for information and/or consulting a health care provider). Results: Women who were exposed to the intervention were significantly more likely to make at least one lifestyle change during the preconception period [adjusted OR 1.56 (95% CI 1.02–2.39)]. Women were especially more likely to preconceptionally reduce or quit [adjusted OR 1.72 (95% CI 1.05–2.83)] their alcohol consumption after exposure to the intervention. Although non-significant, it appeared that women who were exposed to the intervention more often prepared themselves for pregnancy by means of independently searching for preconception health information [adjusted OR 1.13 (95% CI 0.77–1.65)] or consulting a health care provider regarding their wish to conceive [adjusted OR 1.24 (95% CI 0.81–1.92)]. Conclusions: Exposure to a local promotional campaign targeted at preconceptional health was associated with improved preconceptional lifestyle behaviours, especially with regard to alcohol consumption, and has the potential to improve the use of PCC.